Ammonia capture by water splitting and hollow fiber extraction. (31st December 2018) - Yan, Haiyang; Wu, Liang; Wang, Yaoming; Shehzad, Muhammad A.; Xu, Tongwen
Graphical abstract: Highlights: Combination of BMED with HFMCs firstly to capture ammonia from wastewater. Alkali and acid in-situ supplied by water splitting for hollow fiber extraction. The combination process consumes relatively cheap salt Na2 SO4 rather than acid or base. The combination process is of economically competitive due to low energy consumption. Abstract: An efficient method for capturing ammonia from wastewater will effectively solve the ammonia nitrogen pollution in hydrosphere, and the captured ammonia can be utilized potentially as carbon-free energy carriers instead of hydrogen. While the ammonia removal from wastewater has been previously demonstrated, many challenges remain, including indirect ammonia removal, chemicals consumption and secondary pollution. Here, we propose a chemical-free method for ammonia capture by a hybrid system consisting of bipolar membrane electrodialysis (BMED) and hollow fiber membrane contactor (HFMC). It is achieved by taking advantage of the water splitting in BMED as a sustainable "chemical supplier" for hollow fiber extraction. Results indicate that a normalized current density of ∼0.29 mA cm −2 (mg/min) −1 should be applied to BMED unit; the minimum energy consumption is 63.59 kJ/(mol NH4 + -N) for treating the wastewater with NH4 + -N concentration of 200 mg/L; and the ammonia capture ratio can be reached at 65.2%, which can be increased further to >98% through increasing the stages of HFMC modules.